2020
DOI: 10.1108/ijbm-12-2019-0460
|View full text |Cite
|
Sign up to set email alerts
|

Impact of website attributes on customer engagement in banking: a solicitation of stimulus-organism-response theory

Abstract: PurposeThis paper aims to investigate how banking websites can activate customer engagement (CE) to consequently enhance customer trust and retention.Design/methodology/approachUsing an online survey, data were collected from 598 customers of various (public and private) banks in India. Structural equation modeling was used to analyze the data.FindingsResults reveal that the key website attributes viz. website interactivity, website aesthetics, customization, ease of use and telepresence positively affect CE. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
113
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(124 citation statements)
references
References 142 publications
7
113
0
4
Order By: Relevance
“…Scholars have applied the S-O-R model to consumer behavior to explain how environmental stimulus affects consumer behavior through the internal state. Islam [18] used the S-O-R model to investigate how banking websites can activate customer engagement to consequently enhance customer trust and retention. Results revealed that website interactivity, website aesthetics, customization, ease of use, and telepresence positively affect customer engagement.…”
Section: Stimulus-organism-response Modelmentioning
confidence: 99%
“…Scholars have applied the S-O-R model to consumer behavior to explain how environmental stimulus affects consumer behavior through the internal state. Islam [18] used the S-O-R model to investigate how banking websites can activate customer engagement to consequently enhance customer trust and retention. Results revealed that website interactivity, website aesthetics, customization, ease of use, and telepresence positively affect customer engagement.…”
Section: Stimulus-organism-response Modelmentioning
confidence: 99%
“…Forth, as regards the research concentrated solely on the hospitality industry, it is possible to identify the other factors (e.g. customer engagement, customer experience, affective commitment, service innovation and corporate social responsibility; Rather and Parrey, 2018; Raza et al , 2020) influencing outcome favourability, SSR and loyalty in other industries and across different contexts (Islam et al , 2020; Rather, 2018c). It is recommended that future research be undertaken in areas of education, retailing, destination, banking, or professional services.…”
Section: Discussionmentioning
confidence: 99%
“…Building upon this rationale, banks may integrate mindfulness mechanisms within their interactive web framework to stimulate customers' control over their daily spending by enhancing mindful awareness of the present financial actions and its impact on their financial future. Because the key attributes of banking websites play a significant role in customer responses and relationships (Islam et al, 2020), embedding mindfulness-related pop-up messages within the banking website could be another alternative to solicit desired actions from the customers. The use of pop-up messages is based upon empirical evidence for their effectiveness in enhancing people's awareness level by bringing the consciousness level to the present (Monaghan, 2008).…”
Section: Implications For Theory and Public Policymentioning
confidence: 99%